P67 Laryngeal Narrowing In Chronic Obstructive Pulmonary Disease (copd): A Mechanism For Generating Intrinsic Peep?. (10th November 2014) - Baz, M; Haji, GS; Menzies-Gow, A; Tanner, RJ; Hopkinson, NS; Polkey, MI; Hull, JH
Abstract : Introduction and rationale: Patients with COPD often exhibit pursed lip breathing during exercise, a strategy to help overcome a rise in intrinsic PEEP secondary to dynamic hyperinflation. A similar role for laryngeal closure to optimise respiratory mechanics during exertion is postulated. Objectives: Assessment of laryngeal narrowing and its role in exercise intolerance and dynamic hyperinflation in COPD. Methods: and Measurements: We studied 30 age and sex matched subjects (n = 11 healthy, n = 8 mild to moderate COPD, n = 11 severe COPD). Baseline physiological characteristics and clinical status were assessed prior to an incremental maximal cardiopulmonary exercise test with continuous laryngoscopy. Laryngeal narrowing was calculated at the glottic and supra-glottic aperture at rest and peak exercise. Results: Expiratory laryngeal narrowing was pronounced in patients with COPD at rest and peak exercise and related to FEV 1 (r=-0.53, p < 0.05 and r=-0.70, p < 0.001 respectively). Glottic narrowing at peak exercise correlated with inspiratory duty cycle time (Ti/Ttot) (Figure ), this was not seen at rest (r=-0.79, P < 0.0001 and r=-0.07, p = 0.77 respectively). Laryngeal closure at peak exercise inversely correlated with peak oxygen uptake (r=-0.68, p < 0.01). Conclusion: Dynamic laryngeal closure during expiration is prevalent in patients with COPD and is related to disease severity, respiratory duty cycle and exercise capacity.